Pathogenic role of different phenotypes of immune cells in airway allergic diseases: a study based on Mendelian randomization - Xu, Zhihan; Li, Ren; Wang, Leigang; Wu, Yisha; Tian, Yuhe; Su, Yilin; Ma, Yuqiang; Li, Ruiying; Wei, Yao; Zhang, Chen; Han, Shikai; Duan, Siyu; et al. (Frontiers in Immunology, 2024)
Background: Airway allergic disease (AAD) is a class of autoimmune diseases with predominantly Th2-type inflammation, mainly including allergic rhinitis (AR), allergic asthma (AS), and chronic sinusitis (CRS), there are very complex regulatory mechanisms between immune cells and AAD, however, previous reports found that the functions of the same immune cells in AAD are not identical. Objective: The aim of this study was to explore the causal relationship between different phenotypic immune cells and their association with AAD. Method: Utilizing the publicly available Genome-Wide Association Studies (GWAS) database, this study conducted a bidirectional Mendelian randomization (MR) to assess the causal relationship between immune cells of 731 different immunophenotypes and AAD. The primary assessment methods included inverse variance weighting, weighted median, and MR Egger. Additionally, sensitivity analyses such as MR-PRESSO, leave-one-out, and scatter plots were employed to eliminate the interference of heterogeneity and pleiotropy, ensuring the stability of the causal inference. Result: A total of 38 immune cells with different immunophenotypes were found to be positively and causally associated with AR, of which 26 were protective factors and 12 were risk factors. Positive associations were found between 33 immune cells and AS, of which 14 were protective factors and 19 were risk factors, as well as between 39 immune cells and CRS, of which 22 were protective factors and 17 were risk factors. Finally, the results of all relevant immune cells for the 3 diseases were taken and intersected, and it was found that CD3 on CD39+ activated Treg (IVWAR = 0.001, IVWCRS = 0.043, IVWAS = 0.027) may be the key immune cell that inhibits the development of AAD (ORAR = 0.940, ORAS = 0.967, ORCRS = 0.976). Conclusions: This study reveals that different immune phenotypes of immune cells are closely related to AAD at the genetic level, which provides a theoretical basis for future clinical studies.